PERAN PANDANGAN DUNIA ORANG INDONESIA BAGIAN BARAT DALAM MERAMALKAN PRASANGKA TERHADAP ORANG PAPUA - Idhamsyah Eka Putra; Juneman Juneman (MANASA, 2012)
It has been considered that social psychology, particularly the field of prejudice,needs to take part in understanding the social movement and social turmoil in Papua. The goals of this research were to: 1) discover the perceptual themes of the people living in Western Indonesia, about the Papua people (social representation survey), 2) construct scale of measurement of prejudice toward the Papua people (reliability test), 3) examine the relation between two variables which are the worldview and the prejudice toward the Papua people. The participants of this research were 100 students of the University of Indonesia. They were 48% men and the rest were females. Using the reliability proven scale of measurement (α > 0,7 ) it was showed that competitive view of world—that is a description that living in this world is the same as living in the jungle—was one of the determinant factors of prejudice toward the Papua people (γ = 0,49; t > 1,95, in the structural model, where χ2 = 71,48; p > 0,05; RMSEA < 0,05). This finding is not very much different from the social perception of the people living in Western Indonesia about the Papua people. They perceived the Papua people are primitive, having low level of thinking ability, and lack of civilization. This undervalued social perception is typicallyheld by those with competitive view of the world. It is suggested that acquaintanceship and assembly programs will reduce the level of prejudice and will put the Papua people equal with the Indonesians regarding the capability.